Analysis of the Effects of Martial Arts Extracurricular Activities on the Physical Fitness of Junior High School Students - Tasta Puspa Tastia Tastapuspa; Alen Rismayadi; Ivan Rivan Fidaus (Gladi : Jurnal Ilmu Keolahragaan, 2026)
This study aimed to analyze the effect of martial arts extracurricular activities on the physical fitness of junior high school students. The research used a quantitative approach with a pre-experimental one-group pretest–posttest design. The participants consisted of 30 students aged 12–14 years who actively participated in karate, pencak silat, and taekwondo extracurricular activities at SMP Kemala Bhayangkari Bandung. The sampling technique used was purposive sampling. Physical fitness data were collected using a physical fitness test battery for adolescents, including handgrip strength, sargent jump, sit and reach, sit-ups, beep test, and body mass index. Data analysis was conducted using the Shapiro–Wilk normality test, Levene homogeneity test, and one-way ANOVA with a significance level of 0.05. The results showed that all martial arts extracurricular activities improved students’ physical fitness. The one-way ANOVA test showed a significance value of 0.047 (p < 0.05), indicating a significant difference in physical fitness improvement among the three martial arts groups. The karate group demonstrated the highest increase in average scores compared to pencak silat and taekwondo. The differences in improvement were influenced by variations in training frequency, intensity, and movement characteristics in each martial art. Therefore, martial arts extracurricular activities can be considered an effective physical activity program for improving the physical fitness of junior high school students.